Estudo interpretativo da obra "Janissary Music" de Charles Wuorinen : Interpretative study of Charles Wuorinen's "Janissary Music" - Bologna, Ricardo, 1970- (2018)
Orientador: Fernando Augusto de Almeida Hashimoto